Self-Monitoring vs. Implementation Intentions: a Comparison of Behaviour Change Techniques to Improve Sleep Hygiene and Sleep Outcomes in Students - Mairs, L.; Mullan, Barbara (2015)
© 2015, International Society of Behavioral Medicine. Purpose: This study seeks to investigate and compare the efficacy of self-monitoring and implementation intentions—two post-intentional behaviour change techniques—for improving sleep hygiene behaviours and sleep outcomes in university students. Method: Seventy-two undergraduate students completed baseline measures of four sleep hygiene behaviours (making the sleep environment restful, avoiding going to bed hungry/thirsty, avoiding stress/anxiety-provoking activities near bed time and avoiding caffeine in the evening), as well as the Pittsburgh sleep quality index (PSQI) and the insomnia severity index (ISI). Participants were randomly assigned to an active-control diary-keeping, self-monitoring condition or completed implementation intentions for each behaviour. Post-intervention measurement was completed 2 weeks after baseline. Results: Repeated measures analyses of variance found significant main effects of time for improvements in making the sleep environment restful and avoiding going to bed hungry or thirsty, as well as PSQI and ISI scores. Non-significant interactions suggested no group differences on any variable, except for increasing avoidance of stress and anxiety-provoking activities before bed time, for which only implementation intentions were found to be effective. Attrition was higher amongst self-monitoring participants. Conclusion: Both self-monitoring and implementation intentions appear to be promising behaviour change techniques for improving sleep hygiene and sleep. Future research should examine the acceptability of the two behaviour change techniques and the relationship with differential attrition, as well as effect size variations according to behaviour and technique. Researchers should investigate potential additive or interactive effects of the techniques, as they could be utilised in a complementary manner to target different processes in effecting behaviour change.